2014
DOI: 10.1111/apt.12794
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the epidemiology of the hepatobiliary manifestations in patients with inflammatory bowel disease

Abstract: SUMMARY BackgroundExtraintestinal manifestations are frequent in inflammatory bowel diseases (IBD). Most studies published so far focused on viral hepatitis and liver toxicity of IBD-related drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 158 publications
(315 reference statements)
4
85
2
8
Order By: Relevance
“…Of note, these changes in FGF19 also correlated with increased serum C4 (a marker of hepatic BA synthesis), suggesting that low FGF19 might be a relevant driving force for the emergence of BA overproduction and BA malabsorption (BAM), a feature frequently found in CD [88,89]. From a more general point of view, it is also tempting to speculate that alterations of the enterohepatic FGF19 signaling axis could contribute to the pathophysiology of some other liverspecific complications (e.g., gallstone formation, primary sclerosing cholangitis or NAFLD) that are frequently associated with IBD [90][91][92]. Recent studies also started to elucidate the potential role of the BA-FXR-FGF19 axis for other enterohepatic co-morbidities (i.e., short bowel syndrome/intestinal-failure associated liver disease), suggesting that the impact of FGF19 on liver health might be very broad even beyond IBD [93,94].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Of note, these changes in FGF19 also correlated with increased serum C4 (a marker of hepatic BA synthesis), suggesting that low FGF19 might be a relevant driving force for the emergence of BA overproduction and BA malabsorption (BAM), a feature frequently found in CD [88,89]. From a more general point of view, it is also tempting to speculate that alterations of the enterohepatic FGF19 signaling axis could contribute to the pathophysiology of some other liverspecific complications (e.g., gallstone formation, primary sclerosing cholangitis or NAFLD) that are frequently associated with IBD [90][91][92]. Recent studies also started to elucidate the potential role of the BA-FXR-FGF19 axis for other enterohepatic co-morbidities (i.e., short bowel syndrome/intestinal-failure associated liver disease), suggesting that the impact of FGF19 on liver health might be very broad even beyond IBD [93,94].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…A recent systematic review [12] has reported that, in CD patients, the prevalence of cholelithiasis ranged from 11% to 34%, that of primary sclerosing cholangitis (PSC) from 1.2% to 3.4%, that of fatty liver disease was 23%, and hepatic amyloidosis occurred in <1%. Moreover, portal vein thrombosis occurred in 39% to 45% of subjects undergoing proctocolectomy.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, well established that IBD in PSC patients often have a mild colitis but instead run an elevated risk of colorectal cancer. 4,5 In the editorial by Dr Sabino and Dr Torres, 1 they highlight the study's major strength-its size. 1 This is a nationwide study with long follow-up based on national registers.…”
Section: Editorsmentioning
confidence: 99%